If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (13w + 10) + -1(2w + 6) = 0 Reorder the terms: (10 + 13w) + -1(2w + 6) = 0 Remove parenthesis around (10 + 13w) 10 + 13w + -1(2w + 6) = 0 Reorder the terms: 10 + 13w + -1(6 + 2w) = 0 10 + 13w + (6 * -1 + 2w * -1) = 0 10 + 13w + (-6 + -2w) = 0 Reorder the terms: 10 + -6 + 13w + -2w = 0 Combine like terms: 10 + -6 = 4 4 + 13w + -2w = 0 Combine like terms: 13w + -2w = 11w 4 + 11w = 0 Solving 4 + 11w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 11w = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 11w = 0 + -4 11w = 0 + -4 Combine like terms: 0 + -4 = -4 11w = -4 Divide each side by '11'. w = -0.3636363636 Simplifying w = -0.3636363636
| w+s=304 | | 8(w-5)=-40 | | (3x+6)(6x-3)=0 | | 2x^2+12x+8=0 | | 6-3t=3t | | X^2+86x=0 | | (1-7xy+5x^2-y^2)-(6y^2-7xy-6)= | | -(8y+3)-(-7y-6)=-3 | | x^2-8x+5=y | | x^2-8x+5=x | | -(8y+3)-(7y-6)=-3 | | 4(3z-1)-3(2+6)=5(z+1) | | 12-3x+7x=-2(-5x+6) | | n^2-4x-21=0 | | 77=(4+w)(w) | | 5+14t-1=8t+14-4t | | 77=(4w)*(w) | | 0.4(x+0.7)=0.6(x-42) | | 7+16x-4=8x+102-3x | | 5x(4)=16 | | 5x(4)=15 | | x^2=5x+15 | | 15X=-23 | | 7x+2y=6 | | 5-(-3X)=-2 | | 18x+3(4x-9)=-6x+45 | | 32c^15d^14-48c^5d^7=0 | | -(3-p)=-(2p+3) | | a+2=3a-6 | | -3+7x=18 | | 24x^9y^12+40x^3y^3=0 | | 54x^2y^8+12x^2y^4=0 |